GAP ANALYSIS IMPLEMENTASI ISO 26000 PADA PERUSAHAAN PUBLIK - Suwandi, Suwandi; Akyuwen, Roberto (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2019)
ABSTRACT ISO 26000 have been used as a guideline of Corporate Social Responsibility (CSR) practices in various companies globally. This research is aimed at analyzing the implementation gap of two main subjects of ISO 26000 in PT. Bakrie Sumatra Plantations Tbk (BSP). The two main subjects are human rights and labor practices. A descriptive qualitative approach is used to process various primary and secondary data. Primary data are gathered through series of interview with relevant respondents, while secondary data are collected mainly from the CSR reports in the period of 2016-2017. It is found that, if referred to the ISO 26000 core subjects, there is an implementation gap in BSP’s CSR practices in the context of labour practices and human rights. Several important documents on these two core subjects are not yet developed by the BSP management until recently. Keywords: CSR implementation; human rights; ISO 26000; labor practices ABSTRAK ISO 26000 digunakan sebagai panduan praktik Corporate Social Responsibility (CSR) di berbagai perusahaan di dunia. Penelitian ini bertujuan untuk menganalisis kesenjangan (gap) dalam implementasi dua subjek utama dalam ISO 26000 pada PT. Bakrie Sumatra Plantations Tbk (BSP). Kedua subjek utama tersebut adalah hak asasi manusia dan praktik tenaga kerja. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk memproses data primer dan sekunder. Data primer diperoleh dengan metode wawancara dengan responden, sedangkan data sekunder diperoleh dari laporan CSR selama periode 2016-2017. Hasil penelitian ini menunjukkan adanya kesenjangan implementasi di dalam praktik CSR pada BSP, jika ditinjau dari subjek inti ISO 26000, yaitu dalam konteks praktik tenaga kerja dan hak asasi manusia. Beberapa dokumen inti dalam dua subjek utama tersebut belum disediakan oleh manajemen BSP. Kata kunci: implementasi CSR; hak asasi manusia; ISO 26000; praktik tenaga kerja